Peningkatan Kesejahteraan Masyarakat Kelurahan Tembesi Melalui Kolaborasi Pemberdayaan Masyarakat PT Perusahaan Gas Negara (Offtake Stasiun Panaran) Dengan Politeknik Pariwisata Batam - Frangky Silitonga; Suprayogi; Chindy Respa; Rio Zakarias Widyandaru; Endang Reforyani; Alfina Aulia Bintang (SIGMA : Jurnal Sinergi Mengabdi, 2024)
The community empowerment program which is one of the implementations of PT Perusahaan Gas Negara Tbk's CSR (Corporate Social Responsibility) activities - Panaran Station Offtake in Tembesi Village aims to make a positive contribution to the local community through various initiatives and activities that have a social, economic and social impact. environment. Several specific objectives of the PT Perusahaan Gas Negara Tbk - Panaran Station Offtake CSR program for the Tembesi Village community include: Economic Empowerment: Increasing the community's economic capacity through entrepreneurship training, and developing MSMEs (Micro, Small and Medium Enterprises). Education: Counseling to overcome juvenile delinquency, in the form of outreach activities regarding the dangers of drugs and types of countermeasures. Health: Providing education through counseling regarding stunting to the community, assisting posyandu for toddlers and the elderly, as well as providing additional food assistance (BMT) as an effort to improve the quality of health of pregnant women and toddlers, as well as. Social Infrastructure: Providing financial assistance for mosque repairs. Environment: Capacity Building of Agro Green Women Farmer Groups (KWT) and Development of Waste Bank Groups. Through this CSR program, PT Perusahaan Gas Negara Tbk - Panaran Station Offtake seeks to provide a sustainable positive impact on the community of Tembesi Village, as well as supporting inclusive and sustainable development in the area.